1884 Miss. Laws 412, ch. 390, § 24, pt. 16. - (:unkn) unknown (General Publisher, 1884)
To regulate and prevent the storage of cotton, hay, gun powder, oil or any other combustible, explosive or inflammable [sic] material or substance; or of any material or substance offensive to public comfort or injurious to health.
--
Keywords: GUN POWDER STORAGE